2019
DOI: 10.1002/rra.3423
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the functional recognition of aesthetics, hydrology, and quality in urban stream restoration through the framework of environmental perception

Abstract: This study explores the application of a civic perception analysis in the context of stream restoration as a social-ecological system (SES). Analysing such a SES is useful for understanding correlations between civic interests and environmental conditions in river restoration. An analytic hierarchy process (AHP) analysis was used to quantify the demand for restoration objectives. Additionally, an image-based survey was used to precisely capture residents' perceptions of urban stream restoration by comparing ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…While the current study reveals some interesting aspects of how individual's sociodemographic characteristics and perception of the sites are related to flood risk perception, other factors can be considered for future research. Studies have shown that individual's professions and safety concerns and neighbourhood characteristics such as the number of casualties (Slovic, 2016; Slovic & Peters, 2016; Slovic & Weber, 2002), employment rate (Rufat, 2015), crime rates (Brownson, Hoehner, Day, Forsyth, & Sallis, 2009), and protection of natural habitats and landscape aesthetics (Brownson et al, 2009; Hong, Chang, & Chung, 2019) are associated with risk perception and the use of space. Additionally, since the survey respondents were chosen by those who were already using the space, the findings of the study may not reflect the perceptions of the entire population living the study watershed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the current study reveals some interesting aspects of how individual's sociodemographic characteristics and perception of the sites are related to flood risk perception, other factors can be considered for future research. Studies have shown that individual's professions and safety concerns and neighbourhood characteristics such as the number of casualties (Slovic, 2016; Slovic & Peters, 2016; Slovic & Weber, 2002), employment rate (Rufat, 2015), crime rates (Brownson, Hoehner, Day, Forsyth, & Sallis, 2009), and protection of natural habitats and landscape aesthetics (Brownson et al, 2009; Hong, Chang, & Chung, 2019) are associated with risk perception and the use of space. Additionally, since the survey respondents were chosen by those who were already using the space, the findings of the study may not reflect the perceptions of the entire population living the study watershed.…”
Section: Discussionmentioning
confidence: 99%
“…In the respondent groups of S4, the participants who showed a (Slovic, 2016;Slovic & Peters, 2016;Slovic & Weber, 2002), employment rate (Rufat, 2015), crime rates (Brownson, Hoehner, Day, Forsyth, & Sallis, 2009), and protection of natural habitats and landscape aesthetics (Brownson et al, 2009;Hong, Chang, & Chung, 2019) are associated with risk perception and the use of space. Additionally, since the survey respondents were chosen by those who were already using the space, the findings of the study may not reflect the perceptions of the entire population living the study watershed.…”
Section: Landscape Effects and Individual Willingness To Environmenmentioning
confidence: 99%
“…The majority of survey-based studies focus on the general public (Figure 1.7). They often target residents of a neighborhood or town near to a restored river site (e.g., Tunstall et al 2000;Perni et al 2012;Seidl and Stauffacher 2013;Hong et al 2019). They are also interested in the users and visitors of the sites, whether or not they are residents (e.g.…”
Section: Practices Supposed To Guide the Values Associated With Riversmentioning
confidence: 99%
“…It is therefore often mobilized for the aesthetic or landscape evaluation of different restoration scenarios (e.g. Chin et al 2008;Junker and Buchecker 2008;McCormick et al 2015;Hong et al 2019). Preference is also a benchmarking process that is very often invoked in economic evaluations (Hausman 2011).…”
Section: Preferencementioning
confidence: 99%
“…Social and industrial changes in the Ahn-Yang negatively influenced the water quality and ecosystem of the Ahn-Yang stream [19]. Ultimately, the severe contamination of the Ahn-Yang stream prompted citizen stakeholder groups to work together for the stream restoration [20,21].…”
Section: Ahn-yang Streammentioning
confidence: 99%